Application of MCNP for determining the distribution of absorbed dose in lung brachytherapy by using radiation γ 131cs. (May 2019) - Setiawati, E; Pratama, Y; Azam, M
Abstract: One of the MCNP applications is to determine the radiation dose distribution in the brachytherapy process. In this research performed the calculation of the distribution of radiation doses in the lung organ and some organs at risk, so it can be known whether the doses received by the surrounding organs are still within normal limits or not. The American Association of Physicists in Medicine (AAPM) recommends that the doses administered in patient radiotherapy have inaccuracies that are allowed to be within the range of ± 5 %. This simulation is used to determine the energy of γ-radiation absorbed per particle transformation in the lung organ and other organs around it. The radioactive source used is 131 Cs in the form of points with activity varying from 1.7 mCi to 2.3 mCi, and the number of seeds grown varies from 10 to 60. The simulation of the geometry of the human body is made up of phantom ORNL-MIRD. This research made left lung geometry as target organ with density 0, 296 g / cm 3 and located at a Cartesian coordinate position that is (8, 5; 0; 43, 5). From the absorbed dose can be calculated dose distribution on each organ including the target organ and the surrounding organ. If the target organ is considered to receive a dose of 100%, then the surrounding organs are left an atrial wall of 59.58%, left atrium content of 14.32%, left a ventricular wall of 11.62%, left the ventricular content of 15.5 % and right lung by 0.17%. From the results of the dose distribution can be said that the organs that exist around the target organs are still safe because receiving a radiation dose is still below 60%.